Prevalence of resistance associated polymorphisms in Plasmodium falciparum field isolates from southern Pakistan - Ghanchi, Najia Karim (2011)
Background: Scarce data are available on Plasmodium falciparum anti-malarial drug resistance in Pakistan. The aim of this study was, therefore, to determine the prevalence of P. falciparum resistance associated polymorphisms in field isolates from southern Pakistan. Methods: Blood samples from 244 patients with blood-slide confirmed P. falciparum mono-infections were collected between 2005-2007. Single nucleotide polymorphisms in the P. falciparum chloroquine resistance transporter (pfcrt K76T), multi drug resistance (pfmdr1 N86Y), dihydrofolate reductase (pfdhfr A16V, N51I, C59R, S108N, I164L) and dihydropteroate synthetase (pfdhps A436S, G437A and E540K) genes and pfmdr1 gene copy numbers were determined using PCR based methods. Results: The prevalence of pfcrt 76T and pfmdr1 86Y was 93% and 57%, respectively. The prevalence of pfdhfr double mutations 59R + 108N/51R + 108N was 92%. The pfdhfr triple mutation (51I, 59R, 108N) occurred in 3% of samples. The pfdhfr (51I, 59R, 108N) and pfdhps (437G, 540E) quintuple mutation was found in one isolate. Pfdhps 437G was observed in 51% and 540E in 1% of the isolates. One isolate had two pfmdr1 copies and carried the pfmdr1 86Y and pfcrt 76T alleles. Conclusions: The results indicate high prevalence of in vivo resistance to chloroquine, whereas high grade resistance to sulphadoxine-pyrimethamine does not appear to be widespread among P. falciparum in southern Pakistan.